2020
DOI: 10.5614/j.eng.technol.sci.2020.52.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Reconnaissance on Liquefaction-induced Flow Failure Caused by the 2018 Mw 7.5 Sulawesi Earthquake, Palu, Indonesia

Abstract: Long-distance flow failure on gently sloping ground.  Sand boiling and subsidence due to soil liquefaction around the flow failure areas.  Inundated freshwater and springs found even two weeks after the earthquake inside the affected areas, showing the possibility of the existence of a confined aquifer.  A proposed mechanism of long-distance flow failure due to the presence of a confined aquifer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 5 publications
0
10
0
1
Order By: Relevance
“…Figure 4 shows geological map in Palu and Petobo area. [12] In Palu city, [14] indicated the sand, silt and clay of Formation Qap are at various depths between 1-7.2 m. [15] investigated using portable dynamic cone penetration tests in Petobo area. They found that the converted SPT-N values are lower than 10 at the site with depths less than 6.5 m, indicating the sandy soils should be loose to very loose.…”
Section: Geologymentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4 shows geological map in Palu and Petobo area. [12] In Palu city, [14] indicated the sand, silt and clay of Formation Qap are at various depths between 1-7.2 m. [15] investigated using portable dynamic cone penetration tests in Petobo area. They found that the converted SPT-N values are lower than 10 at the site with depths less than 6.5 m, indicating the sandy soils should be loose to very loose.…”
Section: Geologymentioning
confidence: 99%
“…Consequently, water could freely seep into the ground and increase localized groundwater tables. [15] suggested that the slide induced by liquefaction in Petobo would probably be related to the pressures from the confined aquifers. Their post-slide investigations revealed the groundwater levels of the area ranged 0.85-1.1 m deep from the ground.…”
Section: Groundwatermentioning
confidence: 99%
“…According to the theory of stress-wave propagation (Shen et al, 2019b;Hidayat et al, 2020;Luo et al, 2020;Zhao et al, 2021b;Hazarika et al, 2021), a compressional seismic wave will be reflected into a tensile wave when it meets a structural defect during propagation; this could increase the acceleration across the defect. As a result, tensile fractures may have formed as the reflected waves and incident waves were superposed.…”
Section: Triggering Instability Process Of Emeishan Basaltic Rock Massmentioning
confidence: 99%
“…Misalnya, gempa tektonik di zona subduksi (interplate earthquakes) akibat tumbukan antar lempeng yang memicu tsunami berdampak global dengan pelepasan energi seismik berkekuatan relatif besar 𝑀 𝑤 9,0 terjadi di Sumatera-Andaman pada tanggal 26 Desember 2004 (Ishii et al, 2005;Nuannin et al, 2005;Pollitz et al, 2006). Selain itu, gempa akibat aktivitas sesar di sepanjang zona patahan (intraplate earthquakes) juga bisa memicu tsunami yang mematikan, seperti gempa pemicu tsunami di Palu yang dipicu oleh aktivitas sesar Palu-Koro pada tanggal 28 September 2018 dengan magnitudo 𝑀 𝑤 7,5 (Jamelot et al, 2019;Hidayat et al, 2020).…”
Section: Pendahuluanunclassified